[Rezension von: Jews and Christians - parting ways in the first two centuries CE? : reflections on the gains and losses of a model] - Marcus, Joel 1951-; Jews and Christians: parting ways in the first two centuries C.E.? Reflections on the gains and losses of a model 2019 Berlin (2022)
No abstract is available.
Keywords: Rezension